Intellectual Capital Disclosure in Indonesian Banks: The Role of Board of Commissioners - Rizky Ramdani; Bima Cinintya Pratama; Hadi Pramono; Nur Isna Inayati (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to examine the effect of meeting frequency, and multiple boards of commissioner's positions on Intellectual Capital Disclosure with institutional ownership as a moderating variable. This study used a sample of 41 conventional banks during the 2017-2022 period. To test the research hypothesis using panel data regression model analysis. The analysis techniques used in this study were descriptive statistical tests, preliminary tests (Breusch-Pagan, Likelihood tests, Hausman tests), diagnostic tests (heteroscedasticity tests and autocorrelation tests), and hypothesis testing. This study also shows that institutional ownership weakens the relationship between the number of board of commissioners' meetings and Intellectual Capital Disclosure and institutional ownership affects the relationship between multiple boards of commissioners' positions and Intellectual Capital Disclosure.